Patient and public involvement (PPI) in prisons: the involvement of people living in prison in the research process – a systematic scoping review - Samantha Treacy (BMC, 2021)
Abstract Background Patient and Public Involvement (PPI) in health and social care research is increasingly prevalent and is promoted in policy as a means of improving the validity of research. This also applies to people living in prison and using social care services. Whilst evidence for the effectiveness of PPI was limited and reviews of its application in prisons were not found, the infancy of the evidence base and moral and ethical reasons for involvement mean that PPI continues to be advocated in the community and in prisons. Objectives To conduct a review of the literature regarding the involvement of people or persons living in prison (PLiP) in health and social care research focused on: (i) aims; (ii) types of involvement; (iii) evaluations and findings; (iv) barriers and solutions; and (v) feasibility of undertaking a systematic review. Methods A systematic scoping review was undertaken following Arksey and O’Malley’s (International Journal of Social Research Methodology 8: 19-32, 2005) five-stage framework. A comprehensive search was conducted involving ten electronic databases up until December 2020 using patient involvement and context related search terms. A review-specific spreadsheet was created following the PICO formula, and a narrative synthesis approach was taken to answer the research questions. PRISMA guidelines were followed in reporting. Results 39 papers were selected for inclusion in the review. The majority of these took a ‘participatory’ approach to prisoner involvement, which occurred at most stages during the research process except for more ‘higher’ level research operations (funding applications and project management), and only one study was led by PLiPs. Few studies involved an evaluation of the involvement of PLiP, and this was mostly PLiP or researcher reflections without formal or independent analysis, and largely reported a positive impact. Barriers to the involvement of PLiP coalesced around power differences and prison bureaucracy. Conclusion Given the very high risk of bias arising from the available ‘evaluations’, it was not possible to derive firm conclusions about the effectiveness of PLiP involvement in the research process. In addition, given the state of the evidence base, it was felt that a systematic review would not be feasible until more evaluations were undertaken using a range of methodologies to develop the field further.